Factors Affected the Firm Value of the Mining Sector that Go Public in Indonesia - Azhar Latief; Reynaldy Prasetyo (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2022)
The firm value becomes the main focus in terms of decision-making by investors to invest in a company or not. Tobin's Q ratio is one of the financial ratios used to measure firm value. This study aims to analyze how profitability, company size, leverage, and price-earnings ratios affected the firm value of mining companies listed on the Indonesia Stock Exchange from 2016 to 2018. The sample selection technique used was purposive sampling and obtained 33 mining subsector companies with a research period of 3 years (pooled data). The data analysis technique used in this study is Structural Equation Modelling-Partial Least Square (SEM-PLS). The results of this study show that partial profitability and leverage have a positive significant effect on the firm value. On the other hand, partial size and price-earnings ratio didn't have a significant effect on the firm value.